2021
DOI: 10.3390/ph14040361
|View full text |Cite
|
Sign up to set email alerts
|

New InhA Inhibitors Based on Expanded Triclosan and Di-Triclosan Analogues to Develop a New Treatment for Tuberculosis

Abstract: The emergence of multidrug-resistant (MDR) and extensively drug-resistant (XDR) tuberculosis (TB) has reinforced the need for the development of new anti-TB drugs. The first line drug isoniazid inhibits InhA. This is a prodrug requiring activation by the enzyme KatG. Mutations in KatG have largely contributed to clinical isoniazid resistance. We aimed to design new ‘direct’ InhA inhibitors that obviate the need for activation by KatG, circumventing pre-existing resistance. In silico molecular modelling was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…InhA has an active site where catalytic residues Lys165 and Tyr158 are located in the substrate-binding pocket interacting with the long-chain fatty acyl substrates required for the synthesis of mycolic acid ( 75 , 78 ). INH is a prodrug that is oxidized by KatG creating the INH-NAD adduct, a competent InhA inhibitor ( 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…InhA has an active site where catalytic residues Lys165 and Tyr158 are located in the substrate-binding pocket interacting with the long-chain fatty acyl substrates required for the synthesis of mycolic acid ( 75 , 78 ). INH is a prodrug that is oxidized by KatG creating the INH-NAD adduct, a competent InhA inhibitor ( 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…It inhibits blood-stage Plasmodium , via its action against dihydrofolate reductase, and the liver stage of the parasite, via the inhibition of ENR [ 85 ]. Several recent studies are aimed at obtaining new analogs of TCS that are more active and less toxic than the parent compound [ 86 , 87 ].…”
Section: Pharmacological Activities Of Tcsmentioning
confidence: 99%
“…In order to generate analogs which overcome resistance, the development of direct InhA inhibitors which do not require activation shows promise. Early work on triclosan and its derivatives confirmed that it was possible to develop alternative inhibitors for InhA (Armstrong et al, 2020;Rodriguez et al, 2020;Chetty et al, 2021) and multiple scaffolds, as well as a natural product, have been identified which can inhibit InhA (Pan and Tonge, 2012). These newer analogs generally do not require activation and bind directly to InhA, thus they can overcome resistance due to KatG and InhA mutation.…”
Section: New Inha Inhibitorsmentioning
confidence: 99%